The complete chloroplast genome sequence of Ormosia formosana. Issue 3 (2nd July 2020) - Wang, Zheng-Feng; Chang, Li-Wan; Lian, Ju-Yu; Cao, Hong-Lin
Abstract: Ormosia formosana is an important hardwood species and its seeds are popular as decorative jewelry. Currently, this species is threatened in the natural forests due to habitat destruction. Here, we first report the chloroplast genome of O. formosana for future studies in ecology, phylogeny, and conservation. The chloroplast genome of O. formosana is 173, 587 bp in length with a GC content of 35.80%. It includes a large single-copy region of 73, 550 bp, a small single-copy region of 18, 683 bp, and two inverted repeat regions of 40, 696 bp and 40, 658 bp, respectively. The genome was totally annotated with 135 genes, including 90 protein-coding genes, eight ribosomal RNA genes, and 37 transfer RNA genes. Phylogenetic analysis indicated that O. formosana is most genetically similar to O. boluoensis .